Evaluation of peripherin in biofluids of patients with motor neuron diseases. Issue 8 (15th July 2021) - Sabbatini, Daniele; Raggi, Flavia; Ruggero, Susanna; Seguso, Mara; Mandrioli, Jessica; Cagnin, Annachiara; Briani, Chiara; Toffanin, Elisabetta; Gizzi, Matteo; Fortuna, Andrea; Bello, Luca; Pegoraro, Elena; et al.
Abstract: Peripherin (PRPH), a type III intermediate filament, assembles with neurofilaments in neurons of the peripheral nervous system, including lower motor neurons (LMN). To evaluate the role of PRPH in LMN degeneration, we assessed PRPH and neurofilament light chain (NfL) in cerebrospinal fluid (CSF) and serum of 91 patients with motor neuron diseases (MND) and 69 controls. Overall, we found PRPH to be more concentrated in serum than in CSF. Serum PRPH resulted significantly increased in MND patients but it was unrelated to CSF‐NfL or survival in the amyotrophic lateral sclerosis (ALS) subset. PRPH might represent a marker of LMN involvement.